Improving Student Learning Outcomes in Fiqh Learning through the Student Problem Based Learning Model at MI Nurul Jihad - Muzanni; Najla (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning motivation of fifth grade students of MI Nurul Jihad in the subject of Fiqh through the application of the Problem Based Learning learning model. The background of the study identified that the learning process tends to focus on memorization, does not involve students actively, and results in low learning motivation. This condition is influenced by limited facilities and infrastructure, lack of mastery of science and technology by teachers, and low student interest in learning. Based on these problems, this classroom action research was formulated to answer the question: